Studi Kasus Gangguan Proses Pembelajaran Matematika Di Sd Negeri 6 Tanjung - Bagoes Pribadi , Muhammad; Ahmad Suriansyah; Arta Mulya Budi Harsono; Herti Prastitasari; Mubarok (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
This research aims to identify the factors that cause disruption to the mathematics learning process in grade 5 students at SD Negeri 6 Tanjung, as well as understanding the impact of these disruptions on student learning outcomes. This research uses a descriptive qualitative approach through observations and interviews with students and homeroom teachers. The findings show that difficulties in learning mathematics are caused by internal factors, such as students' low interest, motivation, and negative attitudes towards learning, as well as external factors, including teachers' less varied learning strategies, a non-conducive classroom atmosphere, and the minimal role of the family in supporting learning in House. Uncreative learning strategies cause students to become passive, while a busy classroom atmosphere disrupts student focus. Family factors, such as lack of parental guidance, also worsen students' learning conditions. This research suggests the need for a more interactive learning approach, good classroom management, and active family involvement to create a conducive and effective learning atmosphere.